Financial and Business Cycles in Brazil - Krznar, Ivo.; Matheson, Troy. (Washington, D.C. : International Monetary Fund, 2017)
This paper explores the nexus between the financial cycle and business cycle in Brazil. Cycles are estimated using a variety of commonly-used statistical methods and with a small, semistructural model of the Brazilian economy. An advantage of using the model-based approach is that financial and business cycles can be jointly estimated, allowing information from all key economic relationships to be used in a consistent way. The results show that Brazil is now in the downturn phase of the financial cycle. Moreover, the results underscore the importance of macro-financial linkages and highlight risks to the recovery going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet